Enhancing HR Frequency for Precise Genome Editing in Plants - Chen, Hao; Neubauer, Matthew; Wang, Jack P. (Frontiers in Plant Science, 2022)
Gene-editing tools, such as Zinc-fingers, TALENs, and CRISPR-Cas, have fostered a new frontier in the genetic improvement of plants across the tree of life. In eukaryotes, genome editing occurs primarily through two DNA repair pathways: non-homologous end joining (NHEJ) and homologous recombination (HR). NHEJ is the primary mechanism in higher plants, but it is unpredictable and often results in undesired mutations, frameshift insertions, and deletions. Homology-directed repair (HDR), which proceeds through HR, is typically the preferred editing method by genetic engineers. HR-mediated gene editing can enable error-free editing by incorporating a sequence provided by a donor template. However, the low frequency of native HR in plants is a barrier to attaining efficient plant genome engineering. This review summarizes various strategies implemented to increase the frequency of HDR in plant cells. Such strategies include methods for targeting double-strand DNA breaks, optimizing donor sequences, altering plant DNA repair machinery, and environmental factors shown to influence HR frequency in plants. Through the use and further refinement of these methods, HR-based gene editing may one day be commonplace in plants, as it is in other systems.